Perancangan Sistem Informasi Desa Menggunakan Exteme Programming - Putri, Rohana (Journal of Information Technology, Software Engineering and Computer Science (ITSECS), 2024)
The Village Information System (SID) is an information technology-based platform designed to support data management, public services, and decision-making at the village level. SID enables the collection, storage, and processing of data related to population, infrastructure, economic potential, and village development programs in an integrated manner. Prior to the implementation of SID, data management and administrative services at the village level often faced various problems. One of the main problems is the lack of regularity and accuracy in data recording, which is often still done manually, making it prone to errors and duplication. This hinders the decision-making process that requires valid and real-time data. The purpose of this study is to design an effective and efficient village information system by using the Extreme Programming (XP) method as an adaptive and collaborative software development approach, so that a platform that is able to support data-based decision-making, community participation, and innovation towards the implementation of a sustainable digital village. With the XP approach, the design of village information systems becomes more dynamic, allowing for closer collaboration between developers and users, and ensuring that the system can adapt quickly to changes in needs or new challenges that arise. The test results using the ISO 25010 standard, the village information system designed with the Extreme Programming method successfully met all the characteristics of software quality with a success rate of 100%, indicating that the system is feasible to be implemented in a real environment.